Estimating the environmental impact of inappropriate laboratory testing - Lippi, Giuseppe; Daves, Massimo (Journal of Laboratory and Precision Medicine, 2017)
In a recent letter commenting a previous article published in the Journal of Laboratory and Precision Medicine (1), Joseph Watine has outlined an intriguing and almost overlooked consequence of inappropriate laboratory testing, i.e., the potential impact of redundant or unnecessary tests on environmental protection (2). Notwithstanding this concept is theoretically straightforward, Watine failed to provide significant data in support of this statement, which hence remains hypothetical in essence.